Use of virtual reality to remotely train healthcare professionals in paediatric emergency tracheostomy skills: protocol for a multi-centre, non-inferiority educational interventional study with historical controls - Jonathan R. Abbas; Noorulanne Younis; Emily Johnstone; Azita Rajai; Rachel Isba; Antony Payton; Brendan A. McGrath; Neil Tolley; Iain A. Bruce (BMC Surgery)
Abstract Background The insertion of a tracheostomy is an established technique used to wean patients off ventilatory support, manage secretions in complex conditions, and as a potentially life-saving procedure to bypass upper airway obstruction. Life-threatening complications during aftercare are not uncommon and may be influenced by a lack of education of carers or healthcare providers of children and young people living with a tracheostomy. Education programmes designed and supported by the National Tracheostomy Safety Project are effective, but resources are not available to educate the workforce at scale. With the overarching aim of widening access to paediatric tracheostomy skills training, we present the protocol for the development and evaluation of a novel virtual reality (VR) training tool designed to simulate the emergency management of paediatric tracheostomy complications. Methods and discussion A multi-centre, non-inferiority educational interventional study with historical controls will be used to evaluate the novel VR training package. A group of 69 healthcare staff and students will have one week to use the educational intervention as often as necessary to learn paediatric emergency tracheostomy skills. The primary outcome measure is skill performance in simulation in a pre- and post-intervention structure within subjects. Participant performance will also be assessed using non-inferiority metrics against historical traditional educational control data. Secondary outcomes include knowledge gain, knowledge retention, usability, side effects, and participant satisfaction. To minimise the risk of cybersickness, teleportation was the preferred locomotion method for the user navigation within the VR environment. Trial registration Full registration of this study was completed at ClinicalTrials.gov. The registration number is NCT06350708 and was accepted on the 4th April 2024.